Cosmo Innes and the defence of Scotland's past c. 1825-1875 - Marsden, Richard A., 1978- (Ashgate Publishing Limited, 2014)
The antiquary Cosmo Innes (1798-1874) was a prolific editor of medieval and early modern documents relating to Scotland's parliament, legal system, burghs, universities, aristocratic families and pre-Reformation church. This book, which analyses Innes's work and provides sources, opens a window onto the ways in which Scottish identity and ideas about the 'national past' were perceived in Scotland during the nineteenth century, a period when union with England was all but unquestioned.